Conflict, Peace and Development in the Caribbean
XXII, 294 p.
Keywords: One in a series on global political economy, aiming to provide overviews and case studies of states and sectors in the international division of labour. The studies in this volume focus on the regional case of the Caribbean, addressing security, diplomacy, hegemony and development.